2016
DOI: 10.1159/000458446
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Differences between Human Papillomavirus-Related and Human Papillomavirus-Unrelated Oropharyngeal Carcinoma on Diffusion-Weighted Imaging

Abstract: Background and Purpose: Human papilloma virus-related oropharyngeal carcinoma (HPV+ OPC) is a unique entity compared to HPV-unrelated (HPV-) OPC. Previous studies were inconclusive regarding the differences between HPV+ and HPV- OPCs on diffusion-weighted imaging (DWI). This study sought to determine if there is an association between HPV status and apparent diffusion coefficient (ADC) values as an imaging biomarker in OPCs. Materials and Methods: OPC patients with pretreatment MRI including DWI were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 34 publications
5
26
2
Order By: Relevance
“…HPV-negative tumors were correlated with high ADC-values (r = 0.452). This is in line with some previous studies [28,[33][34][35], in which higher ADC histogram parameters in HPV-negative patients were found. This was confirmed by Meyer et al [36], who found a negative correlation of high ADC max and ADC SD with low P53 expression in HPVnegative tumors, which lead to minimal cell cycle arrest, senescence or apoptosis [37].…”
Section: Tablesupporting
confidence: 93%
“…HPV-negative tumors were correlated with high ADC-values (r = 0.452). This is in line with some previous studies [28,[33][34][35], in which higher ADC histogram parameters in HPV-negative patients were found. This was confirmed by Meyer et al [36], who found a negative correlation of high ADC max and ADC SD with low P53 expression in HPVnegative tumors, which lead to minimal cell cycle arrest, senescence or apoptosis [37].…”
Section: Tablesupporting
confidence: 93%
“…23,24 Eventually, five studies were included in the meta-analysis. [8][9][10]25,26 Study characteristics and quality assessment Tables 1 and 2 summarize the patients' characteristics, scanner details, imaging protocol, lesion segmentation method, and HPV status index test. All studies were retrospective.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…A noninvasive imaging biomarker such as ADC could play a substantial role in prognostication and treatment planning, with the additional benefits of being able to evaluate the whole tumor volume and having the potential for repeatability compared to tissue sampling. [8][9][10][11][12] There are currently a limited number of studies evaluating the difference in ADC values of HPV-positive versus HPV-negative HNSCC. Therefore, we performed a meta-analysis to compare the average ADC value of primary tumor lesions between the HPV-positive versus HPV-negative forms of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The classical description of HPV-positive oropharyngeal cancer histology is non-keratinizing and basaloid differentiated SCC as opposed to keratinizing and poorly differentiated form which is commonly seen with HPVnegative forms (52). This histopathological difference has perhaps lent itself to the difference in ADC characteristics of HPV-positive versus HPV-negative oropharyngeal SCC (53)(54)(55)(56)(57). Recent studies have generally reported a lower mean ADC in primary lesion of HPV-positive oropharyngeal SCC compared to the HPV-negative form ( Table 3).…”
Section: Prediction Of Human Papilloma Virus (Hpv) Statusmentioning
confidence: 99%